77 Routine outpatients visits during SARS-CoV2 global pandemic. (17th December 2020) - Fedele, Teresa; Orefice, Silvia; Fiorillo, Ludovica; Cuomo, Vittoria; Capone, Valentina; Casciano, Ofelia; Luciano, Federica; Canonico, Mario Enrico; Santoro, Ciro; Esposito, Roberta
Abstract: Aims: The inability to carry office visits was collateral damage caused by the Coronavirus (COVID-19) pandemic. Tele-health is a relatively new, and yet fundamental amid the current crisis, resource to bridge the gap between phisicians and patients. Methods and results: We report our experience with telemedicine and describe the major events occured in our patients. 121 consecutive adult patients with arterial hypertension (F/M: 56/65; mean age: 66.8 years) were enrolled. 33 patients (27%) had also diabetes, 94 (78%) were also affected from dyslipidemia and 11 (9%) had CAD. They all referred to our ambulatory of hypertension, in most of case for several years. Given the impossibility to continue routine outpatient visits during lockdown, they were all phone called by three residents in order to detect their state of health or any events they could have experienced over this period. They were all asked about their own blood pressure values, the occurrence of new symptoms and of new-onset both cardiovascular and non cardiovascular events. We also followed a self-made preset form. 31 of them (26%) experienced cardiovascular symptoms/events during this period: 11 had hypertensive peaks, in one case associated with nausea and vomiting while 2 of them had hypotensive episodes; 10 had typical angina and/or dyspnoea while 4 had atypical angina; 6 had palpitations; 1 of them developed new onset atrial fibrillation resolved with pharmacologic cardioversion during hospitalization; 1 had syncope; 1 patient reported new onset peripheral oedema; 2 patients died during lockdown for non cardiovascular causes. 17 of them also developed non cardiovascular symptoms, 7 of whom were severe anxiety and/or panic attacks. Almost all patients had important lifestyle changes, in 15 cases (12.3%) associated with weight increase. Conclusion: The impossibility to access to routine outpatient visits during lockdown due to global pandemic of SARS-CoV2, has brought out the risk of underestimating consequences of chronic disease, in absence of appropriate Follow-up. Nevertheless, the two deaths we report were not related to cardiovascular disease. The risk is that both the missing of cardiovascular control visit and the extension of the waiting list, could provoke serious complications in patients suffering from chronic cardiovascular disease.